Methodological proposals for developing trustworthy recommendations of integrative Chinese-Western medicine - Honghao Lai; Mingyao Sun; Bei Pan; Baojin Han; Tingting Lu; Lei Fang; Jie Liu; Long Ge (Integrative Medicine Research)
Background: To refine the methods of developing clinical practice guidelines (CPGs) for integrative Chinese-Western medicine (ICWM), promoting the formation of trustworthy, implementable recommendations that integrate the strengths of Chinese and Western medicine. Methods: Using a nominal group technique (NGT) approach, a multidisciplinary expert panel was established. The panel identified key methodological issues in ICWM-CPG development through literature review and iterative discussions, and formulated methodological proposals to address these issues. The final set of proposals was achieved through consensus among the panel members. Results: The collaborative effort resulted in the identification of five pivotal methodological issues and the subsequent establishment of 22 specific recommendations. These encompass strict adherence to renowned standards, such as those proposed by the Institute of Medicine (IOM) and Guidelines International Network (G-I-N), the employment of methodologies like the GRADE approach and RIGHT statement, the strategic constitution of a balanced development group, the adept identification of ICWM-focused clinical inquiries, the nuanced integration of diverse evidence sources, and the detailed crafting of transparent, implementable recommendations. Conclusions: This study concentrates on the most crucial and prevalent methodological issues in ICWM-CPG development, proposing a series of recommendations. These suggestions result from a multidisciplinary expert consensus, aiming to provide methodological guidance for ICWM-CPG developers, building upon the current foundational methodologies.